2021
DOI: 10.1016/j.heliyon.2021.e06747
|View full text |Cite
|
Sign up to set email alerts
|

Impact of knowledge, attitude, and practice on iodized salt consumption at the household level in selected coastal regions of Bangladesh

Abstract: Background: Iodine deficiency disorder is one of the major hidden hunger for poverty-stricken coastal rural areas of Bangladesh. Despite various programs, including universal salt iodization, IDD is significantly persistent due to poverty, inadequate knowledge, poor attitude, and practice of iodized salt consumption. The present study aimed to determine iodine concentration in salt at the household level as well as the magnitude of knowledge, attitude, and practice related to iodized salt utilization and iodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 12 publications
3
13
6
Order By: Relevance
“…Those participants who earned average monthly income of ≥1000 birr with [AOR = 1.03, 95%CI = (0.41, 2.58)] were factors associated to practice of iodized salt in the study area. This finding was supported by study done in Asella Town Arsi Zone, Ethiopia [ 28 ]. All the type of containers used to store salt was one of the factors associated with good practice of iodized salt at household level.…”
Section: Discussionsupporting
confidence: 80%
“…Those participants who earned average monthly income of ≥1000 birr with [AOR = 1.03, 95%CI = (0.41, 2.58)] were factors associated to practice of iodized salt in the study area. This finding was supported by study done in Asella Town Arsi Zone, Ethiopia [ 28 ]. All the type of containers used to store salt was one of the factors associated with good practice of iodized salt at household level.…”
Section: Discussionsupporting
confidence: 80%
“… 17 In the present study the educational status of participants is quite low and 87.2% belong to low socio-economic status. In contrast to another study which was carried out in Bangladesh, 19 a significant correlation was found between knowledge level and educational status (p < 0.05) of participants. 19 …”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to another study which was carried out in Bangladesh, 19 a significant correlation was found between knowledge level and educational status (p < 0.05) of participants. 19 …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Proper and adequate utilization of iodized salt is necessary as iodine can be lost due to different cooking practices such as pressure cooking, boiling, and shallow frying. 3 …”
Section: Introductionmentioning
confidence: 99%